Assessment of loosening and rotational malalignment following knee endoprosthesis or other surgical components - Gemescu, Ioan N.; Rehnitz, Christoph (Seminars in musculoskeletal radiology, 2018)
Total knee arthroplasty (TKA) has significant medical and economic implications. The correct placement of the femoral and tibial components is vital to ensure a functional knee and also low failure and revision surgery rates. This article provides the most relevant information regarding knee endoprosthesis from a radiologic point of view. Basic information on the recommended alignment of the femoral and tibial components in TKA and how to measure them are discussed. We then present the most important axial plane rotational references for the femoral and the tibial components. The optimal coronal alignment, illustrating the axes of the lower limb, and loosening as the major complication are also discussed. Finally, we offer a detailed example of rotational assessment.
Gesehen am 10.12.2019